KNOWLEDGE SHARING IN ECOPRINT SMES: INNOVATION AND SUSTAINABILITY IMPLICATIONS - Suryadi, Dyan Fauziah; Putra, Sinar Dharmayana; Utami, Adya (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study explores the lived experience of knowledge sharing among ecoprintartisans in South Sulawesi, Indonesia, and its implications for innovation andsustainability in creative small and medium enterprises (SMEs). Using aphenomenological approach, in-depth interviews and participant observationswere conducted with local artisans to uncover how tacit and explicit knowledgeare exchanged and interpreted within their communities of practice. The findingsreveal that ecoprint knowledge is predominantly tacit and embodied, transmittedthrough observation, imitation, and shared experience rather than formaldocumentation. Knowledge sharing occurs within strong community networksgrounded in trust and solidarity, facilitated by both physical workshops and digitalplatforms. Openness in sharing—especially of failures—acts as a catalyst forcollective innovation, while the process itself reinforces environmental, economic,and cultural sustainability. This research contributes to extending knowledgemanagement theory beyond corporate settings by demonstrating that in creative,sustainability-oriented SMEs, knowledge sharing functions not merely as amanagerial process but as an ethical, communal, and generative practice thatsustains both innovation and heritage.